Weed growth, nutrient removal and yield of direct-seeded rice as influenced by establishment methods and chemical-cum-mechanical weed management practices. (January 2023) - Pratap, Vijay; Verma, S.K.; Dass, Anchal
Abstract: Direct seeding of rice ( Oryza sativa L.) has since long been viewed as a potential alternative to unsustainable water-intensive transplanted rice (TPR) world-over, but heavy infestation of a variety of weed species limits the large-scale adoption of direct-seeded rice (DSR) cultivation. Hence, a 2-year field investigation was carried-out in a spilt-plot design, at Banaras Hindu University, Varanasi, during rainy seasons of 2016 and 2017 to assess the influence of various crop establishment methods (CEMs) and weed management options (WMs) on diverse weed-flora, nutrient removal by weeds, weed-control efficiency (WCE) and yield of DSR (cv. Rajendra Kasturi). The results revealed that zero-till DSR + residue +  Sesbania brown manure (ZTDSR + R + SBM) was most effective in containing crop-weed competition, lowered density of Echinochloa colona (L.) Link, Echinochloa crusgalli (L.) Beauv., Cynodon dactylon (L.) Pers., Eclipta alba (L.) Hassak., Caesulia axillaris Roxb., Cyperus rotundus L., Cyperus iria L., Fimbristylis miliacea (L.) Vahl. by 63.4% and enhanced grain yield by 22.8%. Further, applying pendimethalin at 1000 g ai ha −1 as PRE. and later post-emergence (POST) spray of chlorimuron + metsulfuron at 4 g ai ha −1 each 20 days after sowing (DAS) supplemented with 1 hand-weeding (HW) 45 DAS was found to be a better weed management option as this treatment recorded the lowest density and nutrient depletion by above mentioned weeds and higher WCE, thereby improving rice yield by 3–19.5% over other studied WMs. Also, the combination of this weed management option with ZTDSR + R + SBM suppressed weeds to a greater extent, restricting weeds to deplete nutrients (N, P and K) from the soil and finally fetched the highest DSR yield. Highlights: Zero-till DSR + residue +  Sesbania brown manure (ZTDSR + R + SBM) enhanced rice grain yield. Use of Pendimethalin (1000 g ai ha −1 ) as PRE. and POST chlorimuron + metsulfuron (4 g ai ha −1 ) is beneficial. The combination of WM with ZTDSR + R + SBM was the best option for improving DSR yield.